Topic Modeling on WhatsApp User Reviews Using Latent Dirichlet Allocation - Kharisudin, Iqbal; Masri'an, Hera (Universitas Negeri Semarang, 2022)
Abstract.Purpose: Topic modeling is a practical algorithm for identifying topics in text data. This study aims to find issues of WhatsApp user reviews using Latent Dirichlet Allocation (LDA) and describe the characteristics of each case.Method: We used 1710 WhatsApp user reviews written 7-13 August 2020 on Google Play. This research was conducted with a qualitative method consisting of five stages: problem identification, data retrieval, preprocessing, modeling, and analysis. The modeling stage consists of making a Document-Term Matrix (DTM), determining the number of iterations and topics, and building a model. We use perplexity as to the indicator in determining the number of iterations and topics. A lower perplexity value indicates a better model performance. The analysis phase includes observations on the top terms and documents to label and describe the characteristics of each topic. Result: Topic modeling produces word-topic and document-topic assignments. The word-topic assignment contains words with high probability (top terms). Document-topic assignment reveals documents that have a high probability (top documents). The topics most frequently discussed were voice and video calls with 104 reviews, 86 reviews of call quality, photo and video quality with 100 reviews, and voice messages with 75 reviews. Novelty: In this research, a topic model has been generated for a user review of the WhatsApp application using Latent Dirichlet Allocation. The number of iterations in the modeling was determined based on the observation of the perplexity value, instead of randomly assigning iterations.